Pesan Islami Film Qorin bagi Perempuan agar Menjaga Diri - Auliya Fathannisa; Askurifai Baksin (Bandung Conference Series: Communication Management, 2024)
Abstract. The development of science and technology especially in the field of communication, makes it easier for people to convey messages. Film is one of the products of communication media, especially mass media, which functions to convey messages to the public. This movie also shows scenes that contain Islamic meanings and values. The purpose of this research is to find out the Islamic message of the movie qorin for women to take care of themselves in terms of denotative, connotative, and connotative meanings. from denotative, connotative and mythical meanings. The methodology in this research uses qualitative methods and a constructivist paradigm. Observations were made by watching and observing each scene and conversation as data and findings were taken, then documented and analyzed. This research uses Roland Barthes' semiotic theory and constructionist representation. Semiotics is the study of signs. Taking the object of research is the Islamic message and self-preservation of women in the movie Qorin and the subject is the actors involved in the film. This data collection uses observation, documentation and premiere methods. Observation is done by observing every scene and sign in the movie. Documentation comes from other sources such as literature and the internet. While the premiere method is taken from the results of interviews with sources. While the data validity test uses source triangulation. The results of this study indicate that there are Islamic messages and self-preservation in the movie Qorin in terms of denotation, connotation and myth. Islamic messages and women's self-preservation can be seen from several verses of the Qur'an, tools made of wood as a form of protection, as well as harassment and information on where to report incidents. Abstrak. Perkembangan ilmu pengetahuan dan teknologi khususnya dalam bidang komunikasi, mempermudah masyarakat untuk bisa menyampaikan pesan. Film merupakan salah satu produk media komunikasi khususnya media massa, yang berfungsi untuk menyampaikan pesan kepada masyarakat. Dalam film ini juga ditampilkan adegan-adegan yang mengandung makna dan nilai-nilai Islami. Tujuan dari penelitian ini adalah untuk mengetahui pesan islami film qorin bagi perempuan agar menjaga diri ditinjau dari makna denotatif, konotatif dan mitos. Metodologi dalam penelitian ini menggunakan metode kualitatif dan paradigma konstruktivis. Pengamatan dilakukan dengan melihat dan mengamati setiap adegan dan percakapan sebagai data dan temuan yang diambil, kemudian didokumentasikan dan dianalisis. Penelitian ini menggunakan teori semiotika Roland Barthes dan representasi kontruksionis. Semiotika adalah ilmu yang mempelajari tanda-tanda. Mengambil objek penelitian yakni pesan islami dan penjagaan diri pada Perempuan dalam film Qorin dan subjeknya aktor yang terlibat dalam film. Pengumpulan data ini menggunakan metode observasi, dokumentasi dan premier. Observasi dilakukan dengan mengamati setiap adegan dan tanda pada film. Dokumentasi bearasal dari sumber lain seperti literatur dan internet. Sedangkan metode premier diambil dari hasil wawancara bersama narasumber. Sementara uji keabsahan data menggunakan triangulasi sumber. Hasil penelitian ini menunjukkan terdapat pesan islami dan penjagaan diri pada film Qorin di tinjau dari denotasi, konotasi dan mitos. Pesan islami dan penjagaan diri Perempuan dapat dilihat dari beberapa ayat Al-Qur’an, alat yang terbuat dari bahan kayu sebagai bentuk perlindungan, serta adanya pelecehan dan informasi tempat melaporkan kejadian.